A physical demands analysis to identify and delineate critical physical tasks for physically demanding US air force occupations. - Baumgartner, Neal; Gruse, Matthew F.; Flerlage, Erin M.; Rhodes, Andrea K.; Hale, Kimberly N. (Work, 2025)
BACKGROUND: Military physical fitness tests and standards often lack a scientific basis. Contrary to this traditional-historical precedent, US Air Force researchers use a "Two-Tier" health (Tier 1) and performance (Tier 2) approach to develop evidence-based criterion physical fitness tests, standards, and training. This study specifically and only addresses a physical demands analysis, the first step in a six-step process to develop Tier 2 occupationally specific, operationally relevant physical fitness tests and standards, and training guidance. OBJECTIVE: This study conducted a physical demands analysis to identify and delineate occupationally specific, operationally relevant critical physical tasks for eight physically demanding US Air Force occupational specialties. METHODS: A comprehensive five part physical demands analysis reviewed duty tasks, conducted focus groups, assessed incumbents, observed operational tasks, and interviewed senior leaders to detail critical physical tasks. RESULTS: The physical demands analysis delineated duty tasks to critical physical tasks for Special Tactics (556 to 40), Pararescue (981 to 50), Tactical Air Control (415 to 44), Special Operations Weather (586 to 50), Explosive Ordnance Disposal (1107 to 39), Security Forces (1286 to 25), Fire and Emergency Services (802 to 39), and Survival, Evasion, Resistance, and Escape (1099 to 25). CONCLUSIONS: The study approach proved efficacious for conducting a thorough physical demands analysis to identify and delineate occupationally specific, operationally relevant critical physical tasks for eight US Air Force physically demanding occupations. Critical physical tasks provide basis for the next overall research process step, developing physical task simulations to link to predictive physical fitness tests and training guidance.